2006
DOI: 10.5433/1679-0375.2006v27n2p121
|View full text |Cite
|
Sign up to set email alerts
|

Um Desenvolvimento Numérico nas Equações Dinâmicas de Sólitons em Fibras Óticas

Abstract: ResumoAvaliamos a resolução numérica de um sistema de equações diferenciais não-lineares, que descreve a propagação de sólitons em fibras óticas dielétricas, por meio do método de elementos finitos, implementado a partir de formulações streamline upwind Petrov-Galerkin (SUPG) e consistent approximate upwind (CAU). Palavras-chave: Fibra ótica. Sóliton. Método de elementos finitos. AbstractIt was evaluated the numerical resolution of a nonlinear differential equations system that describes the solitons propagati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…It should be observed that the perturbed coupled nonlinear Schrödinger differential equations systems, which describe wave propagation in real optical media, do not present analytical solution (Korpinar, 2019). In literature there are several numerical approaches, whose objective is to describe the propagation of perturbed solitons in dielectric environments, most of them using the finite difference method (Cirilo, Natti, Romeiro, Natti, & Oliveira, 2010;Mahboub & Bekhti, 2014;Li, Li, Cao, & Li, 2017) or the finite element method (Queiroz, Natti, Romeiro, & Natti, 2006;Saka, 2012;Karczewska, Rozmej, Szczecinski, & Boguniewicz, 2016). On the other hand, to solve numerically the system of generated equations, authors use various methods like Newton's method (Syafwan, Susanto, Coix, & Malomed, 2012), Crank-Nicolson method (Liang, Khaliq, & Sheng, 2014), Runge-Kutta Method (Shirazi, Solaimani, Farnam, Ghalandari, & Aleomraninejad, 2017), among others (Dehghan & Taleei, 2010;Gupta, Dalal, & Mishra, 2014;Gupta, Dalal, & Mishra, 2015;Choudlhary, Jha, Mishra, & Vandana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It should be observed that the perturbed coupled nonlinear Schrödinger differential equations systems, which describe wave propagation in real optical media, do not present analytical solution (Korpinar, 2019). In literature there are several numerical approaches, whose objective is to describe the propagation of perturbed solitons in dielectric environments, most of them using the finite difference method (Cirilo, Natti, Romeiro, Natti, & Oliveira, 2010;Mahboub & Bekhti, 2014;Li, Li, Cao, & Li, 2017) or the finite element method (Queiroz, Natti, Romeiro, & Natti, 2006;Saka, 2012;Karczewska, Rozmej, Szczecinski, & Boguniewicz, 2016). On the other hand, to solve numerically the system of generated equations, authors use various methods like Newton's method (Syafwan, Susanto, Coix, & Malomed, 2012), Crank-Nicolson method (Liang, Khaliq, & Sheng, 2014), Runge-Kutta Method (Shirazi, Solaimani, Farnam, Ghalandari, & Aleomraninejad, 2017), among others (Dehghan & Taleei, 2010;Gupta, Dalal, & Mishra, 2014;Gupta, Dalal, & Mishra, 2015;Choudlhary, Jha, Mishra, & Vandana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In (QUEIROZ et al, 2006), a adapted numerical procedure provided the numerical solution of (1), when 0 = δ . In the specific case of the propagation of solitons in special optical fibers, and in optimal situations, the walk-off wave phenomenon can be disregarded (ARTIGAS; TORNER; AKHMEDIEV, 1999), which justifies taking 0 = δ in such situations.…”
Section: Solitons In Dielectric Fibersmentioning
confidence: 99%
“…São exemplos de aplicações: escoamentos compressíveis (BONHAUS, 1998), (LE BEAU;, TEZDUYAR, 2006), dinâmica costeira (CARBONEL; GALEÃO), escoamentos bifásicos (SILVA; COUTINHO; PARSONS), dispersão de poluentes e contaminantes (VÁSQUEZ; MEYER, 2005), (MURCIA;LACAZ, 2002), (OLIVEIRA;MEYER, 2006), escoamento confinado com separação (TEZDUYAR; KALRO, 1995), estudo de estabilidade de escoamentos viscoplásticos (BAAIJENS; HULSEN; ANDERSON, 2004), eletromagnetismo (DELIÉGE, 2003) e telecomunicações (QUEIROZ et al, 2006).…”
Section: Revisão Bibliográficaunclassified